THE ROLE OF SATISFACTION IN INCREASING BEHAVIORAL INTENTIONS MEDIATED BY PERCEIVED TRUST - Paskalis Dakhi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to explain the role of satisfaction in increasing tourists' behavioral intentions with perceived trust as a mediator, and to contribute to the development of cultural tourism behavioral theory. Using a qualitative approach with SmartPLS 4 analysis, this study involved 150 local tourists and 25 international tourists visiting Orahili Traditional Village during a three-month observation period. The variables analyzed included satisfaction, perceived trust, and behavioral intentions. The results show that satisfaction has a direct effect on behavioral intentions and an indirect effect through trust as a mediator. This study confirms that trust plays a key role in strengthening the impact of satisfaction on tourist behavior, with important implications for cultural destination management to improve the quality of tourist experiences and relationships.